1999
DOI: 10.1111/j.1468-2982.1999.1901044.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Headache: Long-Term Results of Stationary Versus Ambulatory Withdrawal Therapy

Abstract: Drug-induced headache is a well-known complication of the treatment of primary headache disorders, and its successful management is only possible by withdrawal therapy. However, it is unknown whether ambulatory or stationary withdrawal is the therapy preferred. We conducted a prospective study on the outcome of stationary versus ambulatory withdrawal therapy in patients with drug-induced headache according to the International Headache Society criteria. Out of 257 patients with the diagnosis of drug-induced he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 21 publications
(10 reference statements)
7
49
2
2
Order By: Relevance
“…In addition, the level of adherence to treatment was comparable with all three strategies (almost 90% of the initial sample completed the study). These results are in line with those of a previous German study, which suggested that outpatient and inpatient programmes could be equally effective [31]. Sick leave of 1 or 2 weeks may be needed when patients are detoxified in an outpatient setting.…”
Section: Should Patients Be Managed In Inpatient or Outpatient Withdrsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the level of adherence to treatment was comparable with all three strategies (almost 90% of the initial sample completed the study). These results are in line with those of a previous German study, which suggested that outpatient and inpatient programmes could be equally effective [31]. Sick leave of 1 or 2 weeks may be needed when patients are detoxified in an outpatient setting.…”
Section: Should Patients Be Managed In Inpatient or Outpatient Withdrsupporting
confidence: 91%
“…primary care) of the protocols they suggest remains uncertain. Data from literature indicate that the strategy chosen (outpatient vs. inpatient) is not a significant predictor of the long-term success of withdrawal therapy [31, 32]. …”
Section: Should Patients Be Managed In Inpatient or Outpatient Withdrmentioning
confidence: 99%
“…Our findings in the shunt patients are in accordance with the experience on MOH in non-neurosurgical patients with initial primary or secondary headaches in whom discontinuation of medication overuse segregated the patients in to three groups: 45% improved markedly in frequency, 48% were unchanged and 7% deteriorated slightly 11 15…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, an outpatient treatment can be an alternative for highly motivated and self-disciplined patients who take a single drug or analgesic not containing barbiturates, and who do not have a high level of depression or anxiety [44, 4850]. …”
Section: The Complex Chronic Migraine/medication Overuse Headache Shomentioning
confidence: 99%
“…Other three studies considering a longer observation period (9–35 months) [50, 57, 58] recorded success rates of 60, 70 and 73%, respectively. Studies with a longer follow-up period (4–6 years) found relapse rates between 40 and 60% [56, 5961].…”
Section: The Complex Chronic Migraine/medication Overuse Headache Shomentioning
confidence: 99%